THE SUSTAINABLE DEVELOPMENT OF AREAS IS SIGNIFICANTLY IMPACTED BY THE USAGE OF GEOINFORMATION TECHNOLOGY (Intent Research Scientific Journal, 2023)
In the course of the study the features of application of geo-information systems and technologies in the management of territories are disclosed. The definition of territorial information management systems as information systems for management of territories that provide processes for the development of optimal spatial solutions is based on the use of up-to-date, reliable and complex geo-information necessary for the implementation of the functions of management of the territory by local authorities. It has been established that geo-technologies, "GIS + Internet", transform geographic information into a universal, economically and socially significant subject of consumption. Today it becomes obvious that the use of geo-information systems and technologies at the local level significantly reduces the cost of maintaining a register of spatial information (land, real estate, engineering communications).